Pengaruh Live Shopping Tiktok @Skintific_Indonesia Terhadap Keputusan Pembelian Mahasiswa Program Studi Ilmu Komunikasi Universitas Fajar - Ramadhanty, Firda; Fitriana (Jurnal Publisitas, 2023)
This research aims to find out the methods of da’wah Ustads Abdul Somad (UAS) in preaching the advantages and disadvantages of UAS in preaching through video and the da’wah models developed by UAS in preaching in video media. The method used is the analysis of content in videos found on YouTube. The results showed that the UAS da’wah method is the method of da’wah al-hikmah, mauidzah and billati hiya ahsan. The advantages of UAS lecture videos are light lecture material, easy-to-understand delivery, use of language that is easily understood by all circles, the existence of light jokes, the right arguments, the use of gestures that are under what he said, a loud, loud and firm voice with the right intonation of voice and with good rhetoric. The disadvantage is that the uploaded lecture video is not included in the question and answer session, there are no subtitles, a thick language accent with a Sumatran accent, and many videos are cut. The UAS da’wah model is transformative, actual, and cultural.